Examining the Effects of Language Brokering on Student Identities and Learning Opportunities in Dual Immersion Classrooms - Lee, Jin Sook; Hill-Bonnet, Laura; Raley, Jason (Journal of language, identity, and education, 2011)
In settings where speakers of two or more different languages coexist, language brokering, the act of interpreting and translating between culturally and linguistically different speakers, is commonly practiced. Yet the examination of language brokering and its implications in classroom settings have not received much attention in the literature. The purpose of this study is to better understand how language brokering functions as an organizational tool in dual immersion classroom interactions to position second language (L2) students in ways that support or constrain learning opportunities. Our data suggest that although language-brokering events enable L2 learners to gain access to critical information in learning contexts, they also work to position the language broker as being more "able" in relation to the student receiving the brokering services, whose opportunities to publicly construct an "able" student identity are restricted. However, in dual immersion programs, the continual shifting of linguistic contexts across subject matter provide opportunities for all students, regardless of linguistic background, to take on the role of the broker, thereby, enabling students to renegotiate and reposition their public student identities. The analysis makes possible an understanding of the intended and unintended consequences of language-brokering processes that may provide insights into how to promote more equitable learning opportunities and positive student identities.